Prevalence of self-reported musculoskeletal symptoms among office workers - Janwantanakul, Prawit; Pensri, Praneet; Jiamjarasrangsri, Viroj; Sinsongsook, Thanes (Occupational medicine (Oxford), 2008)
Background To date, no study has investigated the prevalence of self-reported musculoskeletal symptoms in all the body regions in the general population of office workers. Aims To estimate the 12-month prevalence of self-reported musculoskeletal symptoms in the head/neck, shoulders, elbows, wrists/hands, upper back, low back, hips, knees and ankles/feet among office workers. Methods We conducted a cross-sectional survey using a descriptive questionnaire distributed to 2000 office workers in 54 workplaces. Results A total of 1428 subjects (71%) returned the questionnaire, of whom 1185 were eligible for the study. The annual prevalence of self-reported musculoskeletal symptoms attributed to work was 63%. Sites of symptoms, in order of prevalence, were head/neck (42%), low back (34%), upper back (28%), wrists/hands (20%), shoulders (16%), ankles/feet (13%), knees (12%), hips (6%) and elbows (5%). Female office workers were more likely to report symptoms in the head/neck, shoulder, upper back and ankle/foot regions than male counterparts (P < 0.05). Office workers younger than 30 years were more likely to have symptoms in the upper back than those older than 49 years (P < 0.05). Conclusion Musculoskeletal symptoms are common among office workers with a high proportion experiencing symptoms in the spine. The prevalence of musculoskeletal symptoms in some body regions is dependent on gender and age. This indicates a need to develop specific strategies to reduce the occurrence of such symptoms among office workers.